Kemampuan Berpikir Kritis Matematis Peserta Didik Kelas IX SMP Negeri 13 Tanjungpinang Ditinjau dari Minat Belajar - Estiyani, Estiyani; Liana, Metta; Siregar, Nur Asma Riani (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
The aim of this research is to describe students' mathematical critical thinking abilities as seen from their learning interest. The approach used is a qualitative approach with descriptive research type. This research was conducted in February 2024 at SMP Negeri 13 Tanjungpinang. The research subjects consisted of 1 student from each learning interest category so that the number of subjects was 5 students. The data collection techniques used were questionnaires, tests and interviews. The instruments needed in this research are researchers and are supported by learning interest questionnaires, mathematical critical thinking ability tests and interview guidelines. The data will be analyzed using data collection and conclusion stages in accordance with the Miles and Huberman analysis technique. The data obtained shows that mathematical critical thinking skills with a very high learning interest category are able to fulfill 4 indicators of mathematical critical thinking. then the mathematical critical thinking ability with the high learning interest category is able to fulfill the 4 categories of mathematical critical thinking but is still not complete and precise. Furthermore, critical thinking skills in the moderate learning interest category were only able to fulfill 2 categories while the other 2 categories were not fulfilled. Mathematical critical thinking ability in the learning interest category is only able to fulfill 1 indicator out of 4 indicators of critical thinking ability. And mathematical critical thinking abilities in the very low learning interest category only fulfill 1 of the 4 indicators of mathematical critical thinking abilities.